Physical and mechanical properties of pressure-molded and injection-molded denture base acrylics in different conditions - Yousef A Shibat Al Hamd; Veerendra B Dhuru (Wolters Kluwer Medknow Publications, 2014)
Background and Aim: The aim of the study was to compare the physical (processing shrinkage) and mechanical properties (bending deflection, flexure strength, and flexure modulus) of pressure-molded (Lucitone 199 and ProBase Hot) and injection-molded (SR-Ivocap) denture base materials in different conditions. Materials and Methods: Two denture base materials for pressure molding, Lucitone 199 and ProBase Hot, and one for injection molding (SR-Ivocap) were tested. Polymerization shrinkage (PS) was determined by measuring the linear distances between the reference points on the wax patterns (65 mm × 55 mm × 6 mm) and the corresponding cured acrylic plates and calculating the difference. Rectangular specimens (50 mm × 10 mm × 2.5 mm) were machined from these acrylic plates and used to measure bending deflection (BD) at various load levels, flexure strength (FS), and modulus of elasticity using a three-point bend test on an Instron Universal Testing Machine. A minimum of seven specimens were tested for each variable category. For each material, the percentage of specimens that failed within the load range of 9-10 kg was noted. Statistical analysis involved calculation of mean and standard deviations followed by group comparison of properties of different materials by using analysis of variance (ANOVA) and Tukey's multiple range tests. Level of significance was set at P < 0.05. Result: There was no significant difference between the PS values. ProBase Hot exhibited significantly less BD and greater FS values than the other two materials (P < 0.05). Within the load range of 9-10 kg., 5% of the lucitone specimens, 25% of the SR-Ivocap specimens, and all of the ProBase Hot specimens fractured. Conclusion: The three tested denture base acrylics did not show any significant differences in processing shrinkage. However, ProBase Hot showed significantly lower bending deflection values than Lucitone 199 and SR-Ivocap. Compared to Lucitone 199 and SR-Ivocap, ProBase Hot is a tougher and a stiffer material. Hence, it is more likely to fracture readily if subjected to extreme loading conditions due to the accidental fall of the denture on a hard surface or if the denture wearer inadvertently bites on a particularly hard particle.